1994
DOI: 10.1007/bf01705725
|View full text |Cite
|
Sign up to set email alerts
|

Use of antithrombin III in critical patients

Abstract: The results suggest that the administration of AT III concentrates to critical patients with acquired low levels, but without manifest DIC, may not be justified; although further studies on a larger population are required to establish definite conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…The best replacement therapy is FFP. Clinical studies of antithrombin concentrate in severe blunt trauma and in critical care have shown no benefit [338,339]. …”
Section: Resultsmentioning
confidence: 99%
“…The best replacement therapy is FFP. Clinical studies of antithrombin concentrate in severe blunt trauma and in critical care have shown no benefit [338,339]. …”
Section: Resultsmentioning
confidence: 99%
“…Conventional doses of AT-III, such as 50 U/kg of body weight, have been used clinically to treat sepsis and disseminated intravascular coagulation and to prevent further activation of the clotting cascade associated with consumption of AT-III (2). Because the clotting cascade is also activated after organ transplantation, some groups administer AT-III to patients who have undergone liver transplantation (3).…”
mentioning
confidence: 99%
“…Another prospective, open, randomized trial was published in 1994. 78 In this study, 36 patients with sepsis and multiple trauma were enrolled; 20 patients received AT concentrate, and 16 patients received placebo. Antithrombin was given as a 60 IU/kg loading dose, followed by 10 IU/kg every 6 h. No differences between the two groups were found in hemostasis parameters or evolving APACHE II scores.…”
Section: What Experiences Exist With At Concentrate In Animal Models mentioning
confidence: 99%